A Structural Diversity of Molecular Alkaline‐Earth‐Metal Polyphosphides: From Supramolecular Wheel to Zintl Ion. Issue 56 (3rd September 2021) - Yadav, Ravi; Weber, Martin; Singh, Akhil K.; Münzfeld, Luca; Gramüller, Johannes; Gschwind, Ruth M.; Scheer, Manfred; Roesky, Peter W.
Abstract: A series of molecular group 2 polyphosphides has been synthesized by using air‐stable [Cp*Fe(η 5 ‐P5 )] (Cp*=C5 Me5 ) or white phosphorus as polyphosphorus precursors. Different types of group 2 reagents such as organo‐magnesium, mono‐valent magnesium, and molecular calcium hydride complexes have been investigated to activate these polyphosphorus sources. The organo‐magnesium complex [( Dipp BDI−Mg(CH3 ))2 ] ( Dipp BDI={[2, 6‐ i Pr2 C6 H3 NCMe]2 CH} − ) reacts with [Cp*Fe(η 5 ‐P5 )] to give an unprecedented Mg/Fe‐supramolecular wheel. Kinetically controlled activation of [Cp*Fe(η 5 ‐P5 )] by different mono‐valent magnesium complexes allowed the isolation of Mg‐coordinated formally mono‐ and di‐reduced products of [Cp*Fe(η 5 ‐P5 )]. To obtain the first examples of molecular calcium‐polyphosphides, a molecular calcium hydride complex was used to reduce the aromatic cyclo ‐P5 ring of [Cp*Fe(η 5 ‐P5 )]. The Ca‐Fe‐polyphosphide is also characterized by quantum chemical calculations and compared with the corresponding Mg complex. Moreover, a calcium coordinated Zintl ion (P7 ) 3− was obtained by molecular calcium hydride mediated P4 reduction. Abstract : Mis‐matched : Air stable pentaphosphaferrocene or white phosphorus are used as polyphosphorus source to access molecular group 2 polyphosphides. Structurally diverse polyphosphides ranging supramolecular wheel to Zintl ions have been accessed by using various group 2 reagents such as organo‐magnesium, mono‐valent magnesium or molecular calcium hydride complex. The ancillary ligands and the metal ions influences the structural motifs of the polyphosphides, which was investigated theoretically as well.